Exercise-mediated cerebrovascular repair in Alzheimer's disease: from pathophysiology to therapeutic precision - Cai, Ming; Cai, Keren; Wei, Ziqi; Zhou, Jing; Shu, Jiayi; Wang, Weiyi; Sun, Wanju; Hu, Jingyun (Frontiers in Aging Neuroscience, 2025)
Cerebrovascular dysfunctions, encompassing changes in cerebrovascular microstructure, blood-brain barrier (BBB) integrity, cerebrovascular reactivity, and cerebral blood flow (CBF), accelerate the pathological progression of Alzheimer's disease (AD). Exercise emerges as a promising non-pharmacological intervention that enhances cerebrovascular repair for the treatment of AD. This review summarizes the pathological vascular changes in AD pathology, such as pericyte loss, endothelial dysfunction, and capillary fibrosis, which exacerbate hypoperfusion, hypoxia, and amyloidogenesis. We further discuss the contributing vascular factors and underlying signaling mechanisms to explore potential targets for AD diagnosis and therapy. Finally, we present evidence concerning the impact of exercise on cerebral vascular signaling and the cells involved in vascular plasticity. We also address the impact of various exercise patterns on cerebrovascular health. This work aims to uncover the potential and intervention effects of exercise on cerebrovascular non-malignant alterations and will provide exercise strategies for treating AD.